PENGEMBANGAN MEDIA PRESENTASI BERBASIS PREZI PADA MATERI SISTEM PEREDARAN DARAH MANUSIA UNTUK MELATIH BERPIKIR KRITIS SISWA KELAS XI SMA - Rizki Amaliah Fitri; Mariani Natalina. L; Fitra Suzanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract : Learning presentation media as a tool used to convey learning messages by educators to students. This study aims to develop a Prezi-based presentation media on the human circulatory system material to train critical thinking for class XI high school students. The development of Prezi media was carried out using the ADDIE model until the development stage. on the aspects of media and materials using a validation sheet Prezi-based presentation media obtained an average value of 3.84 with a very valid category. These results show that Prezi-based presentation media on the human circulatory system material developed is very valid with very good quality as a learning medium for class XI high school students The use of Prezi-based presentation media as a learning medium in the material of the human circulatory system class XI SMA can be implemented on a wide scale and can also be redeveloped in the media aspect (software) and in learning materials other biology.Key Words: Prezi media, human circulatory system material, critical thinking